Role of Sirtuins in Linking Metabolic Syndrome with Depression - Song, Juhyun; Kim, Jongpil (Frontiers in Cellular Neuroscience, 2016)
Depression is now widely regarded as a common disabling disorder that affects negatively the social functioning all over the world. Depression is associated with diverse phenomenon in brain such as neuroinflammation, synaptic dysfunction, and cognitive deficit. Recent studies reported that depression occurs by various metabolic changes, leading to metabolic syndrome. Sirtuins are NAD+-dependent class III histone deacetylases, known to regulate diverse biological mechanism such as longevity, genomic stability, and inflammation. The modulation of sirtuin activity has been highlighted as a promising approach to reduce neurodegenerative processes. In this review, we summarize the recent discoveries regarding the potential relationship between sirtuins and depression caused by metabolic disorders. Ultimately, we suggest the possibility that sirtuins will be novel targets to alleviate neuropathogenesis induced by depression.